연구개발에서의 경쟁효과 - 김정욱 (12415, 2012)
This paper investigates the effect of competition on innovative activity. In the research contest, the foremost reason for limiting entry into tournaments is to raise the level of contestant’s effort and to make the ?rms compete so that high value of inn